Reforma ekonomiczna w ZSRR — etapy i perspektywy - Smirnow, Władimir (Wydział Prawa i Administracji UAM, 1990)
The first stage of economic reform in the USSR (1987 - 1988) did not bring any significant practical changes. The crisis on a consumer market has gone deeper, inflation and budget deficit have grown higher and enterprises have still been oriented towards brutto" effects. It is the result of the lack of consistence both in the sphere of shaping formal and legal grounds of the new economic system as well as in the sphere of practical implementation of accepted solutions. The requisite for speeding up the reform is the elimination of bureaucratic machinery of branch system of administration of economy, i.e. the system which obstructs the process of changes. The reform should be carried out in stages. Basic changes should take place in the first half of the 1990s. In the preceding years (1988 -1990) conditions for subsequent reforms must be created, such as rearranging the structure of management, eliminating of influx of inflation money and setting in motion the process of gaining real independence by enterprises. By 1995 basic features of a new economic mechanism should already be fully shaped. In order to achieve this, it is necessary to give up the imperative character of parameters contained in the central plan, to reduce considerably the scope of state obligatory orders and to develop wholesale trade and the market for production goods. The system of economic norms should gradually evolve into a developed, uniform tax system. The latter should become a basic mechanism through which the state influences the decisions of enterprises. The efficiency of anti-inflation policy should be achieved through a two-level banking system and the market for securities. The introduction of fully convertible roubel could be preceded by the implementation of internally convertible roubel, a currency which would supersede the present one. The development of competition depends on the restructuring of economy, the creation of capital market and the influx of foreign capital. The range of centrally determined prices should be limited to goods included in state orders. After 1995 a fully shaped market system should be in operation. It should be regulated by the state by means of a uniform tax system, financial and credit reliefs and state orders. State property should remain only in the areas where other forms of property should prove inefficient. The basic form of property should be the employee stock ownership. The exchange rate of roubel should be shaped by the money market.
Economic reform in the USSR — stages and prospects